ASME 1971 International Gas Turbine Conference and Products Show 1971
DOI: 10.1115/71-gt-58
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Nitrogen Oxides From Gas Turbines by Steam Injection

Abstract: This paper describes the results of tests to determine the effects of steam injection on the production of nitric oxide in gas turbine combustors. When the steam injected into the compressor discharge was 2 percent of the total air flow, the oxides of nitrogen were reduced to 50 percent of what they were with no steam injection for a given load in a gas fired machine. When the steam flow was increased to 4 percent the oxides of nitrogen dropped to 25 percent of the value with no steam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Also, the top of the combustion chamber body is tapped and welded with a thread nut for 10 mm diameter for 4 holes, the distance between each hole to the other is around 20 cm and those holes used as measured points. In the fourth hole is connected with a small T-90-degree pipe with diameter 1 cm and length 40 cm to be the measuring point (11) for the exhaust flue gas analyzer probe. The other holes are used for exhaust gas temperature recording, water injection hole (8) at the fuel nozzle fuel tips, one hole as a spare (9) and the last hole for the flue gas exhaust measuring point (10) to record the NOx [20].…”
Section: Fig 1 Schematic Of the Experimental Test Rigmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the top of the combustion chamber body is tapped and welded with a thread nut for 10 mm diameter for 4 holes, the distance between each hole to the other is around 20 cm and those holes used as measured points. In the fourth hole is connected with a small T-90-degree pipe with diameter 1 cm and length 40 cm to be the measuring point (11) for the exhaust flue gas analyzer probe. The other holes are used for exhaust gas temperature recording, water injection hole (8) at the fuel nozzle fuel tips, one hole as a spare (9) and the last hole for the flue gas exhaust measuring point (10) to record the NOx [20].…”
Section: Fig 1 Schematic Of the Experimental Test Rigmentioning
confidence: 99%
“…The other method is a direct water injection in the gas turbine combustor. Studies showed that with the water injection at the rate of 0.4 of the total air flows, up to 50% of NOx emission can be reduced [11]. The other important point is the proper water injection location and direction [12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the injected steam has been used to cool the gas turbine medium, increasing the total efficiency by approximately 2-3%. 12,13 For water injection, theoretical and experimental results included the computational model values, showing that with 15% water addition in the combustion air, the NOx value was reduced from 15 to 7-8 parts per million, considering the same exhaust temperature owing to the decrease of the oxygen atom concentration. 14 In addition, with water and steam injections, the power output increased from 39 to 43 MW and the NOx emission level decreased from 150 to 73 ppm.…”
Section: Introductionmentioning
confidence: 99%